2013
DOI: 10.1148/radiol.12120376
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Computer-aided Detection as a Second Reader for 6–9-mm Lesions at CT Colonography: Multicenter Prospective Trial

Abstract: efficacy of computer-aided Detection as a second reader for 6-9-mm lesions at cT colonography: Multicenter Prospective Trial 1 Purpose:To assess the effect of computer-aided detection (CAD) as a second reader on the sensitivity and specificity of computed tomographic (CT) colonography in detecting 6-9-mm colorectal cancer (CRC) lesions. Materials and Methods:Individuals with clinical indications for colonoscopy-either for symptoms or as part of participating in a surveillance program or CRC screening-were pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…Strictly speaking, interpretation of CAD marks simultaneously with unannotated regions of the colon should only happen during a "concurrent" reading paradigm [5,16]. In contrast, during a "second-read" paradigm, CAD is activated only after a full unaided interpretation has been performed, in which case the reader's gaze can jump directly from one CAD mark to another [3,4,17]. Therefore, the second-reader paradigm should avoid the problem of gaze being distracted by markers, since CAD is not used during the initial read and only CAD markers need be inspected during the second component.…”
Section: Discussionmentioning
confidence: 99%
“…Strictly speaking, interpretation of CAD marks simultaneously with unannotated regions of the colon should only happen during a "concurrent" reading paradigm [5,16]. In contrast, during a "second-read" paradigm, CAD is activated only after a full unaided interpretation has been performed, in which case the reader's gaze can jump directly from one CAD mark to another [3,4,17]. Therefore, the second-reader paradigm should avoid the problem of gaze being distracted by markers, since CAD is not used during the initial read and only CAD markers need be inspected during the second component.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, on average, reading times are substantially less than those for optical colonoscopy (21)(22)(23). Multiple CT colonography trials with CAD have shown improved reader times, particularly for inexperienced readers, although the use of CAD in secondary mode has been shown to add about 1-3 minutes to the reading time for most cases (24)(25)(26)(27). The increased sensitivity for polyp detection is accompanied by a small decrease in specificity because, often, possible polyps according to CAD are not true polyps (a CAD false-positive result), which can contribute to reader false-positive results.…”
Section: Frequency Of Cad False-positive Resultsmentioning
confidence: 99%
“…Computer-aided detection is designed to decrease errors of detection by identifying and directing the reader to polyp-candidates for further characterization. Several studies have demonstrated increased sensitivity for polyp detection accompanied by a relatively small decrease in specificity due to CAD false-positives which can contribute to reader false-positive results [21][22][23][24].…”
Section: Identifying Polyps Errors Of Detection and Role Of Computermentioning
confidence: 99%